Síndrome do intestino irritável: abordagem geral para diagnóstico, tratamento e acompanhamento - Campestrini, Juliana Damasceno (2022)
Irritable Bowel Syndrome (IBS) is a disease that affects people worldwide, therefore, it has a high prevalence. It is characterized by chronic abdominal pain associated with changes in bowel habits, symptoms can range from: heartburn, epigastric discomfort, headache, low back pain, urinary symptoms and fibromyalgia, the diagnosis of IBS should always be based on symptoms. Considering the difficulty and time required for the diagnosis of this condition, an evaluation is necessary for a better theoretical/practical approach, contributing to the technical-scientific production and consequently early diagnosis and thus providing an improvement in the quality of life of patients affected by this disease. Therefore, this work aimed to describe through a bibliographic review a general/holistic approach to Irritable Bowel Syndrome: For diagnosis, treatment and follow-up. The research has as objective the exploratory character about the Irritable Bowel Syndrome (IBS). The information was obtained from books, scientific articles, technical circulars, Lilacs, Pubmed, Academic Google, Scientific Electronic Library Online (SciELO) Uptodate, VHL and secondary databases, health journals, theses, among other analyzed sources. For this investigation, the following descriptors were used: “irritable bowel syndrome” “Rome criteria” “national consensus for irritable bowel syndrome” “functional colon diseases”, among others. In this context, articles were selected in Portuguese, Spanish and English, the vast majority with a main focus on the diagnosis and treatment of Irritable Bowel Syndrome (IBS). , such as dietary reeducation (reduction of FODMAPs intake), physical exercise, behavioral therapy, pharmacotherapy such as: antispasmodics and linaclotide, probiotics, antidiarrheals, 5-HT3 antagonists, tricyclic antidepressants, etc. However, there is still a need of larger researches that evaluate and prove the effectiveness of the use of different drugs that aim at both the cure and even significant improvement in the quality of life of patients affected by Irritable Bowel Syndrome.